Simultaneous RP-HPLC Method for the Estimation of Formoterol Fumarate and Tiotropium Bromide in Pharmaceutical Dosage Forms - Srinivasu, K.; Venkateswara Rao, J.; Appala Raju, N.; Mukkanti, K. (Asian Journal of Chemistry, 2010)
A simple, fast, sensitive, accurate and precise reverse phase high performance liquid chromatographic method is developed for the simultaneous determination of formoterol fumarate and tiotropium bromide in rotacaps (powder for inhalation) dosage form. A develosil C18-5, 5 μ column having 250 mm × 4.6 mm i.d. in isocratic mode, with mobile phase containing 20 mM KH2PO4:acetonitrile (65:35; pH 3.0) was used. A flow rate of 1.2 mL/min and detection was carried out with 240 nm. The retention times of formoterol fumarate and tiotropium bromide were the 3.6 and 4.7 min, respectively. The method is validated by determining its sensitivity, precision, linearity, accuracy and LOD and LOQ. The proposed method is simple, rapid, sensitive, accurate and precise and so that it can be applied for routine quality control analysis of formoterol fumarate and tiotropium bromide in rotacaps dosage forms.